Environmental impact of milk production from samples of organic and conventional farms in Lombardy (Italy). (20th February 2019) - Pirlo, G.; Lolli, S.
Abstract: In 2016, eight conventional and six organic dairy farmers from the Lombardy Plain were interviewed about their farm technical and economical outcomes in 2015. Environmental performances were assessed according to the life cycle assessment (LCA) approach. The environmental effects investigated were global warming potential (GWP), acidification potential (ACP), and eutrophication potential (EUP). The functional units were 1 kg of fat protein corrected milk (FPCM) and 1 ha of occupied area. The calculations were performed with a version of LatteGHG model, updated to take into account carbon sequestration, ACP and EUP. Herd sizes did not differ between the conventional and organic farms, but the variability in organic herd size (CV 0.88) was larger than that in conventional herd size (CV 0.35). FPCM production was significantly (P < 0.05) higher in the conventional than in the organic farms (9004 vs. 7736 kg/cow per year, respectively). The GWP, ACP and EUP, with no allocation per kilogram of FPCM, for conventional vs. organic farms were 1.24 vs. 1.37 kg CO2 eq, 0.025 vs. 0.026 kg of SO2 eq, and 0.011 and 0.013 kg of PO4 3 − eq, respectively, and showed no significant differences between conventional and organic farms. When considering 1 ha of occupied area, GWP, ACP, and EUP were significantly higher in the conventional than in the organic system (25.8 vs. 11.5 t CO2 eq; 507 vs. 225 g SO2 eq; 210 vs 117 g PO4 3 − eq, respectively). Average milk production was found to be a significant driver of GWP per mass produced and per unit of land occupied in both production systems. Correlations between consumption of inputs per cow or kilograms of milk are controversial. In this study, there was no significant difference in the contribution of sources of GHG, with the exception of inputs for cropping, which was significantly higher in the conventional system. The main contributor of ACP were the emissions of NH3 and NOx from manure management and application, with a significant difference between the conventional and organic systems (82.2% vs. 92.9%, respectively). The main source of EUP was the emissions of NH3, N2 O and P from manure management and application, which was significantly higher in the organic system than in the conventional system (62.9% vs. 67.8%, respectively). These results suggest that organic systems should improve milk productivity, and act as an effective contributor in tackling the environmental problems examined in this study. The study further suggests that there are organic farms with cows producing as much milk as the cows in conventional farms. Highlights: Wide variability of GWP, ACP and EUP per kg of FPCM in the organic dairy farms in northern Italy. GWP, ACP and EUP on 1 kg FPCM are similar in the conventional and organic farms. GWP, ACP and EUP on 1 ha of occupied area are lower in the organic than in the conventional farms.